The potential of Ocean Thermal Energy Conversion (OTEC) in Sabah, Malaysia: A systematic review - Muhammad Fikri Zhafran Mohd Rawi; Rahayu Tasnim; Kua Beng Chu; Jessica Borges Posterari; Fitri Yakub; Mas Omar; Mohamad Naqiuddin Md Mansor; Fikri Akmal Khodzori (Borneo Marine Research Institute, 2024)
Ocean Thermal Energy Conversion (OTEC) is a relatively new technology that leverages on the temperature difference between warm surface seawater and cold deep seawater to generate electricity with no harmful emissions. This type of energy has become an important research topic for sustainable development due to the large energy resources contained in the ocean. Malaysia has a great potential to harness this type of energy due to its long coastline. We studied Sabah's coastal waters for its potential in OTEC. Sabah’s coast is blessed with a range of productive coastal marine ecosystems coupled with several deep-sea islands. These diverse marine features translate into the type of OTEC plant suitable for implementation in Sabah. A systematic literature review (SLR) approach was utilized to compile, review, and assess literature advocating for OTEC, the different types of OTEC plants and analytical methods used in OTEC plant site-selection. We identified five potential sites for OTEC plants in Sabah. These include three sites in the northeast, namely Layang-Layang Island, Mengalum Island, and Mantanani Island, and two sites in the southeast, namely Tawau and Kalumpang. The availability of potential sites in Sabah indicates that the OTEC system – not only as a source of unlimited and environmentally friendly renewable energy, but also as a means of freshwater production – is a viable option for implementation in the State. OTEC systems can be diverted to allocate a portion of the electricity generated for operating adjacent water desalination plants, for generating sample volumes of water suitable for human consumption, and aquaculture and agricultural purposes.